2019
DOI: 10.1093/bioinformatics/btz848
|View full text |Cite
|
Sign up to set email alerts
|

GTDB-Tk: a toolkit to classify genomes with the Genome Taxonomy Database

Abstract: Summary The GTDB Toolkit (GTDB-Tk) provides objective taxonomic assignments for bacterial and archaeal genomes based on the Genome Taxonomy Database (GTDB). GTDB-Tk is computationally efficient and able to classify thousands of draft genomes in parallel. Here we demonstrate the accuracy of the GTDB-Tk taxonomic assignments by evaluating its performance on a phylogenetically diverse set of 10,156 bacterial and archaeal metagenome-assembled genomes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
3,302
2
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 3,636 publications
(3,324 citation statements)
references
References 20 publications
14
3,302
2
6
Order By: Relevance
“…Phylogenetic analysis of the partial 16S rRNA gene (904 bp) confirmed the position of rG16 within the Archaeoglobi ( Supplementary Figure 5 ). The average AAI between rG16 and other Archaeoglobi recovered from the Juan de Fuca Ridge (54.2% ± 0.7 AAI; Supplementary Figure 6 ) and relative evolutionary divergence 33,34 , suggest it is the first representative of a novel family within the Archaeoglobi 35 . The incongruencies between the genome tree and MCR phylogenies for rG16, Ca.…”
Section: Resultsmentioning
confidence: 98%
“…Phylogenetic analysis of the partial 16S rRNA gene (904 bp) confirmed the position of rG16 within the Archaeoglobi ( Supplementary Figure 5 ). The average AAI between rG16 and other Archaeoglobi recovered from the Juan de Fuca Ridge (54.2% ± 0.7 AAI; Supplementary Figure 6 ) and relative evolutionary divergence 33,34 , suggest it is the first representative of a novel family within the Archaeoglobi 35 . The incongruencies between the genome tree and MCR phylogenies for rG16, Ca.…”
Section: Resultsmentioning
confidence: 98%
“…The proposed quantitative species definition allows for the scalable and automated assignment of genomes to species clusters. We have incorporated these species clusters into the GTDB and GTDB-Tk (Chaumeil et al, 2019), an open source tool for the taxonomic classification of genome assemblies. These clusters encompass the nearly 150,000 public genomes within the NCBI Assembly database and will be updated with each GTDB release.…”
Section: Discussionmentioning
confidence: 99%
“…Trees were rooted by randomly selecting a genome from the sister lineage to the genus as determined from the topology of the GTDB R04-RS89 reference trees. The GTDB-Tk v0.3.2 (Chaumeil et al, 2019) 'de novo' workflow with default parameters was used to infer the trees. Briefly, genes were called using Prodigal v2.6.3 (Hyatt et al, 2010) and 120 bacterial or 122 archaeal marker genes identified and aligned using HMMER v3.1b (Eddy, 2011).…”
Section: Assessing Monophyly Of Species Clustersmentioning
confidence: 99%
“…Their classification towards the most up-to-date Thaumarchaeota amoA and 16S rRNA gene databases 2, 43 was performed using BLASTn 45 . Initial classification of genome sequences was performed using classify_wf in the GTDB-Tk package 46 .…”
Section: Methodsmentioning
confidence: 99%